2014
DOI: 10.1016/j.conb.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neural circuits: how stimulus context shapes innate behavior in Drosophila

Abstract: Summary Remarkable advances have been made in recent years in our understanding of innate behavior and the underlying neural circuits. In particular, a wealth of neuromodulatory mechanisms have been uncovered that can alter the input-output relationship of a hereditary neural circuit. It is now clear that this inbuilt flexibility allows animals to modify their behavioral responses according to environmental cues, metabolic demands and physiological states. Here, we discuss recent insights into how modulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Hunger, in turn, promotes the stimulation of food intake [3, 4] and selection of nutritious foods [5]. It also produces enhanced sensory sensitivities and elevated locomotion in insects [6, 7] and mammals [8, 9]. Despite the fact that this process is basic to existence among all types of animals, the mechanism(s) by which hunger triggers feeding and hunger-driven behaviors is not well understood in any animal system.…”
Section: Introductionmentioning
confidence: 99%
“…Hunger, in turn, promotes the stimulation of food intake [3, 4] and selection of nutritious foods [5]. It also produces enhanced sensory sensitivities and elevated locomotion in insects [6, 7] and mammals [8, 9]. Despite the fact that this process is basic to existence among all types of animals, the mechanism(s) by which hunger triggers feeding and hunger-driven behaviors is not well understood in any animal system.…”
Section: Introductionmentioning
confidence: 99%
“…Many neuroendocrine and neuromodulatory pathways also influence satiety and feeding in Drosophila, and have been recently reviewed (Itskov and Ribeiro 2013, Su and Wang 2014. One example is that a method called TANGO (which detects the site of action of endogenous neuromodulators) showed that starvation causes dopamine release in the SEZ, where DopEcR dopamine receptors modulate the gain of sweet receptor terminals (Inagaki et al 2012).…”
Section: Influences Of Hunger and Satietymentioning
confidence: 99%
“…CO 2 , generally repellent to the fly [44], is also a byproduct of fermenting fruit, a strong natural attractant and food source for the fly. A good deal of evidence describes how the olfactory periphery can accommodate the integration of these opposing signals [3] but higher order neural circuits also play a role [15,43**]. Overlapping with the same region of the mushroom body as the CO 2 -responsive glutamatergic MBONs [43**], are a subset of vinegar odor-responsive mushroom body-projecting dopamine-positive PAM neurons that when activated support attraction behavior.…”
Section: Hedonic and Food Cue Processing Along The Mushroom Body Pathwaymentioning
confidence: 99%
“…Prior to initiating feeding, neural systems must integrate food cue information from the external environment with information about internal satiety state to initiate motor programs that drive the search for food [13]. Odors are among the primary cues guiding such foraging behavior.…”
Section: Introductionmentioning
confidence: 99%